2016
DOI: 10.21037/jtd.2016.02.75
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermic circulatory arrest in total arch repair for acute type A aortic dissection: clinical safety and efficacy

Abstract: Moderate HCA is associated with equivalent operative mortality and morbidity and visceral organ functions compared to deep HCA in patients with acute TAAD undergoing total arch replacement under uSACP. This study implies the clinical safety and efficacy of moderate HCA in emergency aortic arch repair for such patients, which provides equivalent cerebral and visceral organ protection while decreasing CPB and cross-clamp times without increasing the risk of operative mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…We compared studies performed only in patients with spinal cord coverage T8 or beyond or 15 cm or greater stent length (n ¼ 6, 201 patients), 15,23,[32][33][34]42 with studies performed only in patients with stent length equal to 10 cm (n ¼ 19, 1634 patients). 15,[17][18][19]21,22,24,25,27,28,33,35,37,[40][41][42]45,46 The patients Figure E1).…”
Section: Subgroup Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We compared studies performed only in patients with spinal cord coverage T8 or beyond or 15 cm or greater stent length (n ¼ 6, 201 patients), 15,23,[32][33][34]42 with studies performed only in patients with stent length equal to 10 cm (n ¼ 19, 1634 patients). 15,[17][18][19]21,22,24,25,27,28,33,35,37,[40][41][42]45,46 The patients Figure E1).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…When we compared studies performed only in patients with acute type A aortic dissection (n ¼ 12, 1300 patients) 21,23,25,[27][28][29][30]35,37,41,46,47 with studies performed only in patients with nonacute type A dissection and aneurysm (n ¼ 14, 741 patients), 14,15,17,19,22,[24][25][26]34,40,[42][43][44][45] we found the following results: The pooled mortality rate was 9.2% (95% CI, 6.9-12.4) in the patients with acute type A and 7.6% (95% CI, 4.9-11.4) in the patients with nonacute dissection and aneurysm (P ¼ .46). The pooled rate of stroke in these 2 groups was 9.3% (95% CI, 4.5-18.5) and 6.6% (95% CI, 3.1-13.5) (P ¼ .51), and the pooled rate of SCI was 2.4% (95% CI, 1.3-4.2) and 5.2% (95% CI, 3.1-8.5) (P ¼ .05), respectively ( Figure E2).…”
Section: Acute Type a Versus Nonacute Type A And Aneurysmmentioning
confidence: 99%
“…In 2016, Gong et al supported our strategy. His study implies the clinical safety and efficacy of MHCA in emergency aortic arch repair, which can provide comparable cerebral and visceral organ protection while decreasing CPB and aortic crossclamp times without increasing the risk of operative mortality and morbidity [18].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, no significant differences were found in the incidence of renal failure or biomarkers of visceral dysfunction between the two cooling techniques as long as the PCT does not exceed 60 minutes (32,33).…”
Section: Dh Vs Moderatementioning
confidence: 98%